Practical data analysis with JMP - Carver, Robert (SAS Institute, 2010)
Uses the powerful interactive and visual approach of JMP to introduce readers to the logic and methods of statistical thinking and data analysis. It includes a myriad of examples and problems that rely on real sets of data, often starting with an important or interesting research question that an investigator has pursued.